The Role Of Governance And Culture On The Sukuk Market In The Islamic Finance Practising Countries - Hersh, Nafez Fayez Ahmad (2023)
Despite being greatly progressive for more than 45 years, covering even Muslim minority countries, the development of Islamic finance and sukuk in some countries is not supported by well-established governance. Through this study, culture has been proposed as the next possible means to improve sukuk industry. Utilizing data from 2012 to 2019 and covering 45 Islamic finance permitting countries, the effect of governance on Islamic finance, culture on Islamic finance, and both governance and culture on the sukuk industry are examined by using generalized method of moments (GMM) estimators. Firstly, the results provide supportive evidence that the governance dimensions have a significant and positive impact on the development of the Islamic finance industry. Secondly, the dynamic GMM results indicate the existence of a significant and positive effect of cultural dimensions such as education, awareness, and time orientation on Islamic finance. Finally, while governance has no significant impact on the sukuk industry, culture has a statistically significant and positive impact on sukuk. In this study, it is suggested to adopt modern financial regulations based on corporate and Shariah governance to enhance the regulatory framework of the Sukuk industry across the globe. Aside from that, the cultural role of education and financial awareness will help countries succeed.